(untitled) (Global Journal of Management and Business Research, 2017)
Technology around us continues to evolve and influence our lives whether we realize it or not. The evolution of technology has enabled people to do more than ever from the comfort of their location with a cell phone signal connected to a smartphone or laptop. Landline phones have become mobile phones for people to communicate anywhere in the world with a cellular signal. Smartphones act as mini computers connected to the internet with the growing number of applications from developers. The speed and computing power of these devices have enabled people to incorporate these devices into their lifestyles. Understanding if these technologies increase or decrease trader’s tendency towards the herding behavior and how it affects their level of confidence is important because it could ultimately affect their trading behaviors. Small-investors are at potential risk because as technology changes, so can the way small-investors trade stocks. Technologies have the ability to influence human behavior in positive or negative way. This study explores the influence of technology on small-investors’ herding behaviors and level of confidence by using a 17 questions survey distributed online and in person. Results from the research, have hinted towards the conclusion that that technology is likely have an increasing effect on stock trader’s herding behavior and level of confidence. Knowledge gained from this research will contribute to area of technology and behavior finance.